P30 CARDIAC ARRESTS IN SPORTS: WHAT IS DIFFERENT COMPARED TO OTHER PUBLIC PLACES?. (18th May 2022) - Compagnoni, S; Gentile, F; Baldi, E; Mare, C; Primi, R; Bendotti, S; Currao, A; Contri, E; Reali, F; Bussi, D; Facchin, F; Centineo, P; et al.
Abstract: Introduction: Cardiac arrests in sports can involve professional athletes, amateurs, but also spectators of sports competitions. Sports facilities are the only ones for which the current law provides for the presence of an automatic external defibrillator (AED) and trained personnel, unlike other public places (schools, work, street, station, general public buildings) where it is only recommended. Objective: To compare patient characteristics, presentation rhythm, bystander cardiopulmonary resuscitation (CPR), AED use before emergency medical services (EMS) arrival, and return of spontaneous circulation (ROSC) longer than 30 seconds in the Utstein category of out–of–hospital cardiac arrests (OHCAs) in sports compared to events in other public places. Materials and Methods: We considered all the OHCAs occurred from 01/01/2015 to 31/12/2020 in the provinces of Pavia, Lodi, Cremona, Mantua and Varese (2400000 inhabitants), excluding the OHCAs occurred at home, in long–term care facilities and witnessed by the EMS. Results: During the study period, 22 OHCAs occurred in sports and 552 in other public places (school, work, street, station, public buildings). The age is similar in the two groups [sport 59 years (IQR 53.5–66.7) vs other 63 years (IQR 51–75), p = 0.2]. In sports, there is a trend in favor of shockable rhythms (13/22=59% vs 185/552=33%, p = 0.1). The percentage of CPR performed by bystanders in sports is significantly higher than in other public places (20/22=91% vs 299/552=54%, p = 0.003), as the bystander AED use (11/22=50% vs 64/552=12%, p < 0.001) and bystander AED shock (7/22=31% vs 27/552=5%, p < 0.001) before EMS arrival. A ROSC greater than 30 seconds was obtained in 59% of OHCAs in sports, with a statistically significant difference compared to events in other public places (13/22=59% vs 166/552=30%, p = 0.015). Conclusions: During sports competitions there is a greater ability to intervene in case of cardiac arrest, which determines a higher probability of obtaining ROSC, although in terms of age or presentation rhythm the patients are comparable to OHCA victims in other places public. These results suggest the need for an AED and trained personnel in other public places as well.